Implementing Ten Types of Innovation Learning for Young Entrepreneurs in Surabaya - Christina Yanita Setyawati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to explain the Ten Types of Innovation learning process for students who already own businesses in Surabaya. The research was conducted at a private university in Surabaya, which implements an entrepreneurship-based curriculum. The study focused on an elective class called the Innovation Class, offered to fifth and seventh-semester students across all programs. The class is completed within one semester, with each session equivalent to 3 credits. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The participants of this study are students and lecturers from five different study programs currently in their fifth and seventh semesters. The findings show that the Innovation Class, held over 16 sessions with three credits per session, enables students to formulate innovations for their businesses. This formulation process involves understanding theoretical concepts, conducting company research, engaging in discussions and mentoring, and concluding with business innovation presentations. The learning process enhances students’ ability to integrate theoretical discussions with company research, improving their business management skills, particularly in business planning. The results also highlight factors influencing learning outcomes, such as student characteristics, available facilities and resources, learning schedules, teaching methods, and evaluation processes. Furthermore, this Innovation Class is essential for students with an entrepreneurial background. The innovative learning process is flexible and can be tailored to meet individual student needs. To further enhance the program, it is recommended that business practitioners provide feedback during presentations. This would offer valuable practical insights, enriching the innovation concepts proposed for the students' businesses.